ANALISIS PENERAPAN AKUNTANSI PERSEDIAAN OBAT-OBATAN BERDASARKAN PSAP NO 5 PADA KANTOR PUSKESMAS PURNAMA KECAMATAN PONTIANAK SELATAN - Prastica, Medy Radea (Jurusan Akuntansi FEB UNTAN, 2024)
This research explores the application of Government Accounting Standard Principles (PSAP) No. 5 in managing medicine supplies at the Purnama Community Health Center Office, South Pontianak. The focus lies in PSAP No. 5, especially in the Presentation of Financial Reports of Non-Profit Organizations at the Community Health Center. Medicines supplies are considered a crucial asset in the provision of effective public health services. Qualitative-descriptive methods were used by collecting data through interviews, observation and document analysis. The research results showed that the Purnama Community Health Center implemented PSAP No. 5 properly and appropriately, contributing to transparency and accountability in the management of medicine supplies. These findings support government accounting principles which emphasize accountability and efficiency in public sector financial management.